Possible Failure Mechanism of Buildings Overturned during the 2011 Great East Japan Tsunami in the Town of Onagawa - Latcharote, Panon; Suppasri, Anawat; Yamashita, Akane; Adriano, Bruno; Koshimura, Shunichi; Kai, Yoshiro; Imamura, Fumihiko (Frontiers in Built Environment, 2017)
Six buildings were overturned in the town of Onagawa during the 2011 Great East Japan tsunami. This study investigates the possible failure mechanisms of building overturning during tsunami flow. The tsunami inundation depth and flow velocity at each overturned building were recalculated by using a tsunami numerical simulation and verified using a recorded video. The overturning moment is a result of hydrodynamic and buoyancy forces, whereas the resisting moment is a result of building self-weight and pile resistance force. This study aimed to demonstrate that the building foundation design is critical for preventing buildings from overturning. The analysis results suggest that buoyancy force can generate a larger overturning moment than hydrodynamic force and the failure of a pile foundation could occur during both ground shaking and tsunami flow. For the pile foundation, pile resistance force plays a significant role due to both tension and shear capacities at the pile head and skin friction capacity between the pile and soil, which can be calculated from 18 soil boring data in Onagawa using a conventional method in the AIJ standards. In addition, soil liquefaction can reduce skin friction capacity between the pile and soil resulting in a decrease of the resisting moment from pile resistance force.